Gains, losses, and life goals identified by caregivers of individuals with disabilities in the United States - Raver, Sharon A.; Michalek, Anne M. P. (Social Welfare: Interdisciplinary Approach, 2011)
It is often reported that caregivers of individuals with disabilities experience stress as they manage caregiving responsibilities while they make the effort to balance family and work. Thirty-one caregivers of individuals with an array of disabilities in the United States completed a qualitative survey in this pilot study that asked them to identify their gains and losses from providing care and to identify their life goals. The gains from caregiving were identifi ed as enhanced empathy and compassion, and the losses as strained family relationships, and less personal time. The most commonly identifi ed life goals were experiencing happiness and achieving financial stability. The implications of these results on professionals’ attempts to support caregivers and their families are discussed.
Keywords: caregivers of children/adults with disabilities; life goals; stress; family relationships; disability policy; disability governmental support